Producción audiovisual como herramienta de difusión turística del sitio ancestral "El Lechero" Pucara alto, Otavalo - Cevallos, Jonathan I. (2018)
The present investigation is about the community of Pucará Alto and the ancestral site of Otavalo Canton, taking into account that it is located in one of the most touristic provinces of Ecuador called the blue province of the lakes and that is not constantly visited site. For this reason, it has been determined to show the true history of the sacred site the milkman and his rituals of purification and thanks to the lands for the food provided, with the realization of an audiovisual product will show the population everything related to the tourist attraction.